Geochemistry of Syntectonic Carbonate Veins Within Late Cretaceous Turbidites, Hikurangi Margin (New Zealand): Implications for a Mid‐Oligocene Age of Subduction Initiation. (10th May 2022) - van de Lagemaat, Suzanna H. A.; Mering, John A.; Kamp, Peter J. J.
Abstract: We document the geochemistry of calcite veins in the Late Cretaceous Tikihore Formation (Raukumara Peninsula, New Zealand) to characterize their fluid composition and source and to help establish the age of subduction initiation at the Hikurangi margin of the Australia‐Pacific plate boundary. The calcite veins occur within normal faults offsetting turbidites that accumulated in a lower slope basin. Vein calcite trace metal content and rare earth element patterns are consistent with a seawater‐derived brine composition. Oxygen isotope (δ 18 O) values range from −6.1 to +8.4‰ and are −0.2‰ VPDB on average; positive δ 13 C values of up to +28‰ VDPB reflect methanogenesis. Oxygen isotope temperature data indicate that calcite vein mineralization occurred at temperatures in the range of 29°C–48°C. This is markedly less than the maximum burial temperature experienced by the host rocks, which we estimate to be 104 ± 10°C at 30–27 Ma from the inverse modeling of apatite fission track data. The vein calcite has a 28.5 ± 4.9 Ma U‐Pb age. From these data, we infer that the succession above Tikihore Formation was removed by slumping, thereby resulting in fluid overpressure in the reservoir, followed by hydraulic fracturing and the precipitation of the vein calcite. Ultimately, the data presented here from the Tikihore veins are consistent with subduction initiation at 30–27 Ma, based on the U‐Pb age of the vein calcite and modeling of apatite fission track data for the host sandstone, corroborated by the 30–27 Ma timing of back thrusting on the Taranaki Fault and related foredeep development in eastern Taranaki Basin. Plain Language Summary: Subduction zones, where, most commonly, an oceanic plate turns down below an overriding continental plate, are among the most dynamic geological settings on Earth. In the frontal part of these zones, known as the forearc region, marine water along with sediments can be transported down the interface of the two plates. One water pathway can be upward into the overriding plate, where it may be trapped in fluid reservoirs. Tectonic processes ultimately fracture these reservoirs, leading to fluids being pumped along these fractures resulting in minerals being precipitated within them. In this study, we analyze the chemistry of a set of calcite veins collected from fracture zones in a sedimentary formation (Tikihore Formation) in the forearc region (Hikurangi margin) of New Zealand. We establish that the fluid source of the veins is indeed marine waters and that they precipitated at relatively cool temperatures (29°C–48°C). Uranium‐lead dating of vein calcite sample material establishes that it was precipitated 28.5 ± 4.9 million years ago. From these data and supporting geological information, we interpret the subduction zone along the Hikurangi margin, which is part of the Australia‐Pacific plate boundary zone through New Zealand, to have started during the interval of 30–27 Ma. Key Points: We geochemically characterize calcite veins in normal faults that offset Cretaceous turbidites These veins record hydraulic fracturing and precipitation after rupturing of a reservoir, following exhumation near the new plate boundary The U‐Pb age of the veins together with other results constrains a mid‐Oligocene timing of subduction initiation at the Hikurangi margin